Which Oxford Knee Score level represents a satisfactory symptom state after undergoing a total knee replacement?. (12th October 2020) - Ingelsrud, Lina H; Terluin, Berend; Gromov, Kirill; Price, Andrew; Beard, David; Troelsen, Anders
Abstract : Background and purpose — Meaningful interpretation of postoperative Oxford Knee Score (OKS) levels is challenging. We established Patient Acceptable Symptoms State (PASS) and Treatment Failure (TF) values for the OKS in patients undergoing primary total knee replacement (TKR) in Denmark. Patients and methods — Data from patients undergoing primary TKR between February 2015 and January 2019 was extracted from the arthroplasty registry at the Copenhagen University Hospital, Hvidovre in Denmark. Data included 3, 12, and 24 months postoperative responses to the OKS and 2 anchor questions asking whether they considered their symptom state to be satisfactory, and if not, whether they considered the treatment to have failed. PASS and TF threshold values were calculated using the adjusted predictive modeling method. Non-parametric bootstrapping was used to derive 95% confidence intervals (CI). Results — Complete 3, 12, and 24 months postoperative data was obtained for 187 of 209 (89%), 884 of 915 (97%), and 575 of 586 (98%) patients, with median ages from 68 to 70 years (59 to 64% female). 72%, 77%, and 79% considered as having satisfactory symptoms, while 6%, 11%, and 11% considered the treatment to have failed, at 3, 12, and 24 months postoperatively, respectively. OKS PASS values (CI) were 27 (26–28), 30 (29–31), and 30 (29–31) at 3, 12, and 24 months postoperatively. TF values were 27 (26–28) and 27 (26–29) at 12 and 24 months postoperatively. Interpretation — The OKS PASS values can be used to guide the interpretation of TKR outcome and support quality assessment in institutional and national registries.